PENGARUH TEKNOLOGI KOMUNIKASI DIGITAL TERHADAP PERTUMBUHAN KARAKTER GENERASI NET DI INDONESIA - Sipra Mariana Gutandjala (Institut Agama Kristen Negeri (IAKN) Ambon, 2018)
The progress of this nation is determined by the character of each generation who is the main pillar of a nation. Character that is certainly built on the basis of the recognition of the values and norms of Pancasila as a solid foundation for each generation in playing their roles and responsibilities in the midst of society. However, with the development of technology, a new challenge for the formation of the character of the young generation of this nation. Add to this the presence of a new sparring culture (popular culture) brought by technology increasingly influencing even at times it could erode the local cultural order of the Indonesian nation. This certainly causes a major crisis in the lives of the younger generation because thus the local culture as one of the pillars of defense and a mirror for the young generation now has to deal with the presence of a new counter-culture which will certainly also have a great influence on the lives of the young generation of the nation this. The identity crisis as well as various other social crises will certainly be experienced by the younger generation. Therefore we need serious attention both from educational institutions, religious institutions, social institutions or family institutions in order to provide assistance and think about character education strategies that are right on target for the young generation in Indonesia considering the presence of technology does not only bring positive impacts but technology also brings impacts negative in life so that various efforts to anticipate the future of Indonesia's young generation become urgent and very important thing to doÂ Keyword: Popular Culture, Identity crisis and Social crisis, the role of educational institutions, religion and family.